Integrating Multichannel Analysis Of Surface Waves And Horizontal To Vertical Spectral Ratio Techniques For Dynamic Site Characterisation At Pulau Pinang, Malaysia - Chibuzor, Anukwu Geraldine (2019)
Pulau Pinang is susceptible to the effects of various forms of ground motion capable of causing damages, and an understanding of the dynamic characteristics of its soils is important for site effects estimation, especially as it concerns site amplification. The HVSR technique is a cheap and easy means of estimating site effect parameters, however, there is no consensus on the use of the HVSR peak amplitude as a substitute for site amplification. The focus of this study is to determine the suitability of utilizing the HVSR peak amplitude as a proxy for site amplification, by developing empirical formulae for site amplification estimation. Also, of importance is the development of an empirical model for estimating the depth to engineering bedrock and microzonation maps for the study area.